System integration and optimization of security in a multilayer virtual network - Nadezhda, Shchegoleva; Kiyamov, Jasur (Computer Tools in Education, 2023)
In modern distributed systems, especially in the field of blockchain and cloud computing, ensuring reliable and efficient consensus is a critical task. This paper discusses a combined consensus approach based on a combination of P-BFT and RAFT protocols. The purpose of this study is to explore the possibilities of a combined P-BFT and RAFT consensus approach to improve reliability, performance and security in distributed registries and cloud systems. The principles of operation and characteristics of each protocol are explored, as well as their joint use to achieve agreement in a distributed environment. In the course of the work, the advantages and prospects of the combined P-BFT and RAFT approach are analyzed, support for various trust models is considered, as well as the integration of data protection mechanisms to ensure security and privacy. The results of the study suggest that the combined P-BFT and RAFT consensus approach demonstrates high performance and reliability in distributed registries and cloud systems. The proposed approach has prospects for application in various areas where a reliable and secure consensus is required to ensure the efficient operation of distributed systems.